THE OPTIMIZATION OF OVAL VARIABLE CROSS-SECTION BEAM IN MEMS - SUN JiangHong; LU KunLei; YI YuanLin; HAN JianNan (Jixie qiangdu)
MEMS device structure plays an important role on the performance of the sensor. To improve its stability, oval variable beam is selected to decrease stress concentration and widen the gap between the non-detection directional stiffness and detection directional stiffness, thereby reducing cross sensitivity and improving stability; To achieve the best dynamic performance, damping ratio ξ should be appropriate and theoretical stiffness of beam is calculated. By establishing the pure bending model of the beam, the stiffness formula and the strength condition of the beam is derived. Under the same rigidity of trapezoidal beam with equal section and trapezoidal variable section beam, the quality of the beam with variable cross section increases slightly, but the stress at the dangerous section decreases greatly.